Scorpionism in Brazil in the years 2000 to 2012 - Reckziegel, Guilherme Carneiro (2014)
Background: Scorpionism is a serious public health problem in Brazil. Nationwide epidemiological analyses of scorpion stings are scarce. In this context, the present study aims to provide an epidemiological analysis of accidents involving scorpions in Brazil. Methods: An analytical epidemiological study of the scorpion accidents reported in the Information System for Notifiable Diseases (SINAN) was conducted from 2000 to 2012 in Brazil. Results: During this period, 482,616 accidents and 728 deaths were reported. The annual average incidence and mortality rates per 100,000 inhabitants were 19.6 and 0.030, respectively, with annual average lethality rate of 0.16%. The highest accident frequency was recorded in male subjects, aged 20–49 years, from September to December and in urban areas, except in the northern region of the country, where accidents were most frequent in June and July, and in rural areas. Males up to age 9 and rural areas were defined as an age group and area for greatest death risk, respectively. Conclusions: Scorpionism in Brazil is a predominantly urban health problem that mostly affects people at an economically active age. The Northeast and Southeast hold the majority of cases and deaths, as well as the highest annual incidence and mortality averages, but the Central West and North presented the highest average annual lethality rates. The epidemiological changes described in this study highlight the need for intensifying health surveillance actions to prevent scorpion accidents in Brazil.